2020
DOI: 10.3390/antiox9111114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Heat Treatment on the Antioxidant Activity of Egg White Protein-Derived Peptides after Simulated In-Vitro Gastrointestinal Digestion

Abstract: The study aimed to analyze pH and heat treatment’s effect in modulating the release of peptides with antioxidant activity after simulated gastrointestinal (GI) digestion of Egg white powder (EWP). EWP samples with neutral (EWPN) and alkaline (EWPA) pH were heat-treated at 20, 60, and 90 °C and analyzed for protein aggregation, solubility, and GI digestibility. Heat treatment decreased solubility and induced protein aggregation, which was higher for EWPN as compared to EWPA. The unfolding of EWPA proteins at 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Similarly, ACE-inhibition with the whole hydrolysate tended to be better in RIR boiled samples compared to boiled, although no significant difference was observed and the tendency did not hold for WLH samples. Following previous studies, we found a discrepancy between chemical and cell-based antioxidant capacity [35,36]. Caution should be taken when interpreting the physiological relevance of whole egg hydrolysates chemical antioxidant capacity, which depends on inherent pathways and metabolism of the cells in question.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similarly, ACE-inhibition with the whole hydrolysate tended to be better in RIR boiled samples compared to boiled, although no significant difference was observed and the tendency did not hold for WLH samples. Following previous studies, we found a discrepancy between chemical and cell-based antioxidant capacity [35,36]. Caution should be taken when interpreting the physiological relevance of whole egg hydrolysates chemical antioxidant capacity, which depends on inherent pathways and metabolism of the cells in question.…”
Section: Discussionsupporting
confidence: 70%
“…The difference between chemical and cellular antioxidant activity can be observed in the CAA assay, where the samples with the highest antioxidant activity in the ORAC assay were unable to reduce the ROS production compared to quercetin, a radical quencher phytochemical [27]. Rao et al, in 2020, suggested that high molecular weight peptides from egg white can potentially exhibit a higher antioxidant activity in ORAC due to their radical quenching capacity independently of their bioavailability [35]. In a physiologically relevant model, the peptides need to be absorbed by the cell to confer their antioxidant activity and quench the intracellular ROS measured in the CAA assay [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rao et al . (2020), the heat treatment at 65 ℃ for 30 min might enhance the release of peptides with potential antioxidant activity. In addition, small peptides (MW < 3 kDa) can form secondary structures, which are the key factors affecting the antioxidant activity of peptides (Zhu et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, static digestion model is widely used to evaluate the effect of food processing on the nutrient bioaccessibility (nutrient released from the food matrix), bioavailability (including nutrient absorption), or allergenic peptides. Several food processing techniques, such as heat-treatment [27][28][29][30], drying [31], curing/aging [32], ultrasonication [33,34], and protein extraction [35], have been employed for numerous food products.…”
Section: Static Digestion Modelmentioning
confidence: 99%